This preview shows pages 1–7. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Lecture Stat 302 Introduction to Probability  Slides 4 AD Jan. 2010 AD () Jan. 2010 1 / 24 Axioms of Probability Consider an experiment with sample space S . For each event E , we assume that a number P ( E ) , the probability of the event E , is de&ned and satis&es the following 3 axioms. Axiom 1 & P ( E ) & 1 Axiom 2 P ( S ) = 1 Axiom 3 . For any sequence of mutually exclusive events f E i g i 1 , i.e. E i \ E j = ? when i 6 = j , then P ( [ i = 1 E i ) = i = 1 P ( E i ) Direct consequences include P ( ? ) = 0 and for mutually exclusive events f E i g i 1 P ( [ n i = 1 E i ) = n i = 1 P ( E i ) . AD () Jan. 2010 2 / 24 Examples Example (coins): Assume both coins are unbiased; i.e. a head is as likely to appear as a tail, then P ( f H , H g ) = P ( f H , T g ) = P ( f T , H g ) = P ( f T , T g ) = 1 4 . Example : A die is rolled and we assume P ( f 1 g ) = P ( f 2 g ) = &&& = P ( f 6 g ) = 1 / 6 . Hence as a consequence from axiom 3, the probability of having an even or odd number is equal to P ( f 1 , 3 , 5 g ) = P ( f 1 g ) + P ( f 3 g ) + P ( f 5 g ) = 1 / 2 , P ( f 2 , 4 , 6 g ) = P ( f 2 g ) + P ( f 4 g ) + P ( f 6 g ) = 1 / 2 . AD () Jan. 2010 3 / 24 Properties Proposition : P ( E c ) = 1 & P ( E ) . We have S = E [ E c and E \ E c = ? so P ( S ) = 1  {z } axiom 2 = P ( E [ E c ) = P ( E ) + P ( E c )  {z } axiom 3 . Proposition : If E F then P ( E ) P ( F ) . We have F = E [ ( E c \ F ) and E \ (( E c \ F )) = ? so P ( F ) = P ( E ) + P ( E c \ F )  {z } 0 by axiom 1 P ( E ) . Proposition : We have P ( E [ F ) = P ( E ) + P ( F ) & P ( E \ F ) . We have E [ F = E [ ( E c \ F ) and E \ (( E c \ F )) = ? so P ( E [ F ) = P ( E [ ( E c \ F )) = P ( E ) + P ( E c \ F ) but F = ( E c \ F ) [ ( E \ F ) with ( E c \ F ) \ ( E \ F ) = ? so P ( F ) = P ( E c \ F ) + P ( E \ F ) ) P ( E c \ F ) = P ( F ) & P ( E \ F ) . AD () Jan. 2010 4 / 24 Example You are in a restaurant and ordering 2 dishes. With proba 0.6, you will like the &rst dish; with proba 0.4, you will like the second dish. With proba 0.3, you will like both of them. What is the proba. you will like neither dish? Let A i the event: "You like dish i . Then the proba you like at least one is P ( A 1 [ A 2 ) = P ( A 1 ) + P ( A 2 ) & P ( A 1 \ A 2 ) = . 6 + . 4 & . 3 = . 7 . The event that you like neither dish is the complement of liking at least one, so P ( " you will like neither dish ) = P (( A 1 [ A 2 ) c ) = 1 & P ( A 1 [ A 2 ) = . 3 AD () Jan. 2010 5 / 24 Example A die is thrown twice and the number on each throw is recorded. Assuming the dice is fair, what is the probability of obtaining at least one 6? There are clearly 6 possible outcomes for the &rst throw and 6 for the second throw. By the counting principle, there are 36 possible outcomes for the two throws. Let A i the event I have obtained a 6 for throw i . The probability we are interested in is P ( A 1 [ A 2 ) = P ( A 1 ) + P ( A 2 ) & P ( A 1 \ A 2 ) = 1 6 + 1 6 & 1 36 = 11 36 ....
View Full
Document
 Spring '10
 222
 Probability

Click to edit the document details